(untitled) (Medico Legal Update, 2020)
Background/Objectives: This study focuses on the psychological problems of college students, which are rapidly deteriorating in recent years, and examines how depression and anxiety affect the psychological well-being and examines the mediating effects on emotional perception clarity. It was done to improve the quality of life by solving them. Method/Statistical Analysis: 317 data were collected for this study. The research method used factor analysis and covariance structure analysis. Findings: Anxiety level of college students did not have a significant effect on emotional clarity. Second, the level of depression in college students had a significant effect on emotional clarity. Third, the emotional perception clarity of college students had a significant effect on psychological well-being. Fourth, anxiety levels did not have a significant effect on psychological well-being. Fifth, the depression level of college students had a significant effect on psychological well-being. Sixth, the mediating effect of emotional perception clarity on the causal relationship between depression level and psychological well-being of college students was found to be partial mediating effect. Improvements/Applications: Based on the results of this study, online self-diagnosis service expansion is required for college students to be aware of their psychological emotional problems, and practical help and training are required to control negative emotional experiences by clearly recognizing emotions. This will provide a foundation for college students to increase their psychological well-being by increasing their ability to respond appropriately to changing circumstances.